Analisis Usaha dan Nilai Tambah Agroindustri Kacang Rondam di Kecamatan Pangururan Kabupaten Samosir - Anju Hasudungan Naibaho; Kustopo Budiraharjo; Wahyu Dyah Prastiwi (SUNGKAI, 2024)
This study aims to analyze costs, revenues, revenues, business feasibility, and analyze the added value of rondam beans. The research location is in Sentra Kacang Rondam, Pangururan District, Samosir Regency, North Sumatra. The research method used was a census with 3 respondents in the rondam bean agroindustry. The analysis methods used are cost analysis, revenue analysis, revenue analysis, business feasibility analysis, Hayami value-added analysis. The results showed production cost of IDR30.520.672.00/month. Receipt of IDR42.750.000,00/month. Revenue of IDR12.229.328.00/month. R/C Ratio of 1,40. ROI of 10%. Payback Period for 9 months 1 day. The added value produced by the rondam bean agroindustry in the process of making rondam beans is IDR14.800/kg. The added value ratio of rondam bean agroindustry of 34,98% is classified as moderate.